Education and Community Services: Synergy for Social Change - Hidayat, Rahmat; Yuswan, Yuswandi; Erwin, Erwin (Journal Ligundi of Community Service, 2024)
Background. Education and community services play integral roles in driving social change. Their synergistic collaboration has the potential to create significant impact and bring about positive transformations in society. Purpose. This study aims to explore the synergies between education and community services and their collective contribution to social change. The research seeks to understand how collaborative efforts between these two sectors can lead to meaningful societal improvements. Method. The research adopts a mixed-methods approach, combining qualitative interviews, surveys, and document analysis. It involves engaging stakeholders from the education and community service sectors to gather diverse insights and perspectives. Results. The findings highlight the effectiveness of synergizing education and community services for social change. Collaborative initiatives led to enhanced community engagement, empowerment, and the development of knowledge and skills among participants. However, challenges such as resource limitations and coordination issues were also identified, underscoring the need for sustainable partnership frameworks and funding mechanisms. Conclusion. The study concludes that the synergistic integration of education and community services is crucial for driving meaningful social change. It emphasizes the importance of effective collaboration, resource allocation, and sustained efforts in achieving long-lasting societal improvements. Recommendations are provided for policymakers, practitioners, and researchers to further leverage the synergies between education and community services for impactful social transformations.